ANALISIS HUBUNGAN KECERDASAN INTERPERSONAL DENGAN KETERAMPILAN PROSES SAINS DASAR MAHASISWA PENDIDIKAN BIOLOGI UNIVERSITAS CENDERAWASIH - St. Rahmadani (Pusat Pengembangan Pendidikan dan Penelitian Indonesia (P4I), 2026)
ABSTRACT Basic science process skills are essential competencies that Biology Education students must possess to support scientific activities. In addition to cognitive factors, interpersonal intelligence is believed to play a role in the development of these skills. However, studies examining the relationship between interpersonal intelligence and basic science process skills among Biology Education students remain limited. Therefore, this study was conducted to provide empirical evidence regarding the relationship between these two variables. This study aimed to determine the relationship between interpersonal intelligence and basic science process skills among Biology Education students at the Faculty of Teacher Training and Education, Cenderawasih University. The study employed a quantitative approach with an associative research design. The research sample consisted of 27 students enrolled in the Basic Biology course during the odd semester of the 2025/2026 academic year. Data were collected using observation sheets of interpersonal intelligence and basic science process skills. The results showed that students' interpersonal intelligence was in the high category, while their basic science process skills ranged from moderate to high. The Chi-Square test results indicated a significant relationship between interpersonal intelligence and the basic science process skills of Biology Education students at the Faculty of Teacher Training and Education, Cenderawasih University; therefore, H₀ was rejected. It can be concluded that there is a significant relationship between interpersonal intelligence and basic science process skills among Biology Education students at the Faculty of Teacher Training and Education, Cenderawasih University. ABSTRAK Keterampilan proses sains dasar merupakan kemampuan penting yang harus dimiliki mahasiswa Pendidikan Biologi dalam kegiatan ilmiah. Selain faktor kognitif, kecerdasan interpersonal diduga berperan dalam mendukung pengembangan keterampilan tersebut. Namun, kajian mengenai hubungan kecerdasan interpersonal dengan keterampilan proses sains dasar pada mahasiswa Pendidikan Biologi masih terbatas. Oleh karena itu, penelitian ini dilakukan untuk memberikan bukti empiris mengenai hubungan kedua variabel tersebut. Penelitian ini bertujuan untuk mengetahui hubungan antara kecerdasan interpersonal dengan keterampilan proses sains dasar mahasiswa Pendidikan Biologi FKIP Universitas Cenderawasih. Penelitian menggunakan pendekatan kuantitatif dengan jenis penelitian asosiatif. Sampel penelitian berjumlah 27 mahasiswa yang menempuh mata kuliah Biologi Dasar semester ganjil tahun akademik 2025/2026. Pengumpulan data dilakukan menggunakan lembar observasi kecerdasan interpersonal dan keterampilan proses sains dasar. Hasil penelitian menunjukkan bahwa kecerdasan interpersonal mahasiswa berada pada kategori tinggi, sedangkan keterampilan proses sains dasar berada pada kategori sedang hingga tinggi. Hasil uji Chi-Square menunjukkan adanya hubungan yang signifikan antara kecerdasan interpersonal dengan keterampilan proses sains dasar mahasiswa Pendidikan Biologi FKIP Universitas Cenderawasih, sehingga H₀ ditolak. Dengan demikian, dapat disimpulkan bahwa terdapat hubungan yang signifikan antara kecerdasan interpersonal dengan keterampilan proses sains dasar mahasiswa Pendidikan Biologi FKIP Universitas Cenderawasih.